Studies on the effectiveness of cefoperazone on subclinical mastitis of dairy cows - Erol ALAÇAM; Tevfik TEKELİ; Yavuz SEZEN; Osman ERGANİŞ (Eurasian Journal of Veterinary Sciences)
In this study the effectiveness of Cefoperazone injected intracisternally against to different bacterias was investigated in subclinically infected cows. The udder quarters of 52 Swedish Red cows W i thin 3-13 years old were used as materials. They were all in the first month of lactation. Quarter samples were screened for the California Mastitis Test (CMT), and milk samples were collected aseptically from the infected udders. After a direct microscopic somatic cell count was carried out on all positive samples, they were cultured and antibiograms were tested. Pathazone (Cefoperazone sodium, 258.8 mg, Pfizer) was injected intracisternally in a single dose to the subclinically infected quarters after evening milking and rested in the quarters at least for 12 hours. Seven days later, the milk samples were collected and cultured again. The samples which are free from the pathogen isolated from the first sample were decided as a cured. The microorganisms isolated from the infected quarters were found to be 50.44% for staphylococcus, 30.75% for streptococcus. The positive results of the treatment were 83.33- 100% in streptococcus and only 44.44% in staphylococcus infections. As a conclusion, Cefoperazone sodium was found effective against to most of the subclinical mastitis agents as they are in the elinical cases.